Analysis and functional characterization of sequence variations in ligand binding domain of thyroid hormone receptors in autism spectrum disorder (ASD) patients. Issue 12 (30th August 2017) - Kalikiri, Mahesh Kumar; Mamidala, Madhu Poornima; Rao, Ananth N.; Rajesh, Vidya
Abstract : Autism spectrum disorder (ASD) is a neuro developmental disorder, reported to be on a rise in the past two decades. Thyroid hormone‐T3 plays an important role in early embryonic and central nervous system development. T3 mediates its function by binding to thyroid hormone receptors, TRα and TRβ. Alterations in T3 levels and thyroid receptor mutations have been earlier implicated in neuropsychiatric disorders and have been linked to environmental toxins. Limited reports from earlier studies have shown the effectiveness of T3 treatment with promising results in children with ASD and that the thyroid hormone levels in these children was also normal. This necessitates the need to explore the genetic variations in the components of the thyroid hormone pathway in ASD children. To achieve this objective, we performed genetic analysis of ligand binding domain of THRA and THRB receptor genes in 30 ASD subjects and in age matched controls from India. Our study for the first time reports novel single nucleotide polymorphisms in the THRA and THRB receptor genes of ASD individuals. Autism Res 2017, 10: 1919–1928 . ©2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Thyroid hormone (T3) and thyroid receptors (TRα and TRβ) are the major components of the thyroid hormone pathway. The link between thyroid pathway and neuronal development is proven in clinical medicine. Since the thyroid hormone levels in Autistic children are normal, variations in their receptors needs to be explored. To achieve this objective, changes in THRA and THRB receptor genes was studied in 30 ASD and normal children from India. The impact of some of these mutations on receptor function was also studied.